REHABILITASI BAGI PENYALAHGUNA NARKOTIKA DALAM PERSPEKTIF MAQASID AS-SYARI’AH - Sirait, Adi Syaputra (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2018)
Criminal Law in Indonesia is currently experiencing a renewal that includes formal criminal, material criminal and its implementation, it can be seen from the matter of Draft Law of the Criminal Code currently being discussed in the House of Representatives, is no exception about the criminal penalty for drug abuse which is now very threatening, many opinions of experts who argued that criminal confinement / imprisonment for narcotics abusers is not epektif because it can not cure and make a deterrent user. The regulation on the implementation of this rehabilitation was previously arranged through the Supreme Court Circular Number 07 Year 2009 to engage drug addicts in rehabilitation centers, with the aim that rehabilitation can be a punishment that heals the psyche and the minds of narcotics abusers who have been damaged due to the narcotics. Rehabilitation efforts for narcotics addicts and victims of narcotics abuse have not been found in the history of Islamic law development or Islamic criminal law, so this discussion should get further attention from the aspects of Islamic law (Maqasid As-Syari'ah) or Islamic criminal law